Strategi Marketing Public Relations dalam Meningkatkan Pengguna Jasa Event Organizer - Arman Tio Leriant Medananda; Mohamad Subur Drajat (Bandung Conference Series: Public Relations, 2022)
Abstract. With the increasingly widespread and more prolific event organizer business at this time so that the world of business competition is certainly getting bigger. So that we need several marketing public relations strategies that can increase interest in using event organizer services Public Relations Marketing Strategy has an important role in promoting services in a company. Including Event Organizer service providers. Companies must be able to promote in various ways such as through the media, internet, or direct marketing. The communication strategy is carried out to achieve a company goal. Marketing public relations strategy is a combination of communication planning and communication management. This research method is descriptive, and uses the theory of three ways strategy marketing public relations The result after implementing this marketing public relations strategy is that Buckley is running quite effectively in the publication of its products and services. It can be seen from the customers who know Buckley's social media and are interested in the contents. The result of applying the pull strategy is that many people know about Buckley decoration. The implementation of the push strategy makes the audience interested in using the services of Buckley Decortion because of the several promotions provided and the pass strategy from Buckley, namely Buckley's interesting and informative content has succeeded in making prospective customers interested in using Buckley's services because potential customers do not hesitate and are sure when will use the services of an Event organizer from Buckley Abstrak. Semakin marak dan semakin berjamurnya bisnis event organizerpada saat ini membuatpersaingan bisnis semakin besar. Sehingga diperlukan beberapa strategi marketing public relations yang dapat meningkatkan minat penggunaan jasa event organizer. Strategi Marketing Public Relations memiliki peran penting dalam mempromosikan jasa dalam sebuah perusahaaan. Termasuk penyedia jasa Event Organizer. Perusahaan harus mampu mempromosikan dengan berbagai macam cara melalui media, internet, atau pemasaran secara langsung. Strategi komunikasi dilakukan untuk mencapai suatu tujuan perusahaaan. Stategi Marketing public relations merupakan paduan dari perencanaan komunikasi dan manajemen komunikasi. Metode penelitian ini adalah deskriptif dan menggunakan teori three ways strateghy marketing public relations. Strategi marketing public relations. Buckley Decoration berjalan cukup efektif dalam publikasi produk-produk jasanya.HasilnyaBisa terlihat dari costumer yang mengetahui media sosial Buckley dan tertarik dengan konten-kontennya. Hasil penerapan pull staregy jadi banyak khalayak yang mengetahui buckley decoration. Penerapan push strategymembuat khalayak tertarik menggunakan jasa Buckley Decortion karena beberapa promosi yang diberikan. Dan penerapan pass strategy dari Buckley yaitu konten-konten Buckley menarik dan informatif berhasil membuat calon costumer tertatik menggunakan jasa dari Buckley karena calon costumer menjadi tidak ragu dan sudah yakin saat akan menggunakan jasa Event organizer dari Buckley.